ANALISIS PERSEPSI DAN MINAT SISWI SMA NEGERI 1 SIDOARJO TERHADAP KARIR STEM MENDUKUNG PENCAPAIAN SDGS 2030 - Nur Ulfa Amelia; Zeni Fradita Sari; Norma Ellya Roziana; Nabil Nazhif Fikri Ahmad; Rayhan Naufarezi; Ardiyansah Ardiyansah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The underrepresentation of women in Science, Technology, Engineering, and Mathematics (STEM) suggests that career choices are shaped not only by academic ability but also by learning experiences and social environments that influence how students envision their future. Against this background, this study explores female students’ perceptions of STEM careers, their career interests, and the factors contributing to the development of those perspectives at the secondary education level. A descriptive qualitative approach was employed involving 15 female students from SMA Negeri 1 Sidoarjo selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and were examined using an interactive analysis process consisting of data reduction, data display, and conclusion drawing, supported by source, technique, and time triangulation. The findings reveal that most participants hold positive perceptions of STEM and believe that women have equal opportunities to succeed in STEM-related fields. Nevertheless, these positive perceptions do not necessarily translate into intentions to pursue STEM careers, as career interests remain influenced by self-efficacy, gender stereotypes, the visibility of women in STEM professions, and social support. These findings highlight the importance of fostering inclusive learning environments, strengthening career literacy, and enhancing social support to encourage women's participation in STEM while providing practical insights for educational strategies aligned with the Sustainable Development Goals (SDGs) 2030. ABSTRAK Kesenjangan representasi perempuan pada bidang Science, Technology, Engineering, and Mathematics (STEM) menunjukkan bahwa pilihan karier tidak semata-mata dipengaruhi oleh kemampuan akademik, tetapi juga oleh pengalaman belajar dan lingkungan yang membentuk cara peserta didik memandang masa depannya. Berangkat dari kondisi tersebut, penelitian ini mengeksplorasi persepsi dan minat siswi terhadap karier STEM serta mengidentifikasi faktor-faktor yang memengaruhi pembentukannya pada jenjang pendidikan menengah. Penelitian menerapkan pendekatan kualitatif deskriptif dengan melibatkan 15 siswi SMA Negeri 1 Sidoarjo yang dipilih melalui purposive sampling. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis secara interaktif dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan yang diperkuat melalui triangulasi. Hasil penelitian menunjukkan bahwa sebagian besar siswi memiliki persepsi positif terhadap STEM dan meyakini bahwa perempuan memiliki kesempatan yang setara untuk berprestasi. Namun, persepsi tersebut belum selalu berkembang menjadi minat memilih karier pada bidang STEM karena masih dipengaruhi oleh self-efficacy, stereotip gender, representasi perempuan dalam profesi, serta dukungan lingkungan sosial. Temuan ini menegaskan bahwa penguatan ekosistem pembelajaran yang inklusif, literasi karier, dan dukungan sosial berperan penting dalam membangun orientasi karier perempuan pada bidang STEM sekaligus memberikan dasar bagi pengembangan strategi pendidikan yang mendukung pencapaian Sustainable Development Goals (SDGs) 2030.